2018
DOI: 10.1177/0391398818790334
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of density-fractionated erythrocytes to subhaemolytic mechanical shear stress

Abstract: Red blood cell populations respond differently to mechanical stimuli: older (more dense) cells are highly susceptible to sublethal mechanical trauma, while cell age (density) does not appear to alter the magnitude of improved cell deformability following low-shear conditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
(45 reference statements)
1
16
0
Order By: Relevance
“…20 It is possible that venesection treatment positively affects the subhemolytic threshold of RBCs by increasing RBC turnover and thus also reducing the relative proportion of older and oxidatively damaged RBC, which have reduced mechanical properties. 28 It has been reported that venesection therapy decreased oxidative stress markers and increased the bioavailability of various antioxidants 23 ; these findings support that the improved mechanical properties in the present study subsequent to venesection therapy may be related to an improved redox state of RBCs. Although speculative, it is important to consider that serum ferritin is considered an important inflammatory marker, 34 and thus the decrease in serum ferritin observed in the current study may also suggest a decrease in systemic inflammation of volunteers, potentially contributing to the improved cell mechanics.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…20 It is possible that venesection treatment positively affects the subhemolytic threshold of RBCs by increasing RBC turnover and thus also reducing the relative proportion of older and oxidatively damaged RBC, which have reduced mechanical properties. 28 It has been reported that venesection therapy decreased oxidative stress markers and increased the bioavailability of various antioxidants 23 ; these findings support that the improved mechanical properties in the present study subsequent to venesection therapy may be related to an improved redox state of RBCs. Although speculative, it is important to consider that serum ferritin is considered an important inflammatory marker, 34 and thus the decrease in serum ferritin observed in the current study may also suggest a decrease in systemic inflammation of volunteers, potentially contributing to the improved cell mechanics.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, while a single venesection may remove longer circulating (ie, older) RBCs, decreases in blood volume concurrently increase circulating levels of erythropoietin (ie, the hormonal stimulus for erythropoiesis), 27 thus triggering increased synthesis of younger RBC with improved mechanical capabilities. 28 Collectively, our data suggest that venesection therapy is effective at improving cellular deformability in HH; however, it may be of clinical value to examine whether these improvements translate to enhanced microcirculatory function in individuals with HH. Given that it has been recently demonstrated that impaired cell mechanics, at least in sickle cell disease, negatively impacts microcirculatory function and tissue oxygenation, 16 this area of investigation appears meaningful.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This heterogenic response for the shear elastic modulus of single RBCs following exposure to sublethal mechanical stress has not been previously reported, and precise mechanisms dictating (non)response to shear damage remain to be elucidated. Recent work 34 presents a plausible explanation, however, for such disparity in the present individual cell responses: Subpopulations that arise due to physiological “aging” respond differently to mechanical shear, where the most dense RBCs (older cells) accumulate shear rigidification at more than twice the rate of the less dense counterparts (younger cells).…”
Section: Discussionmentioning
confidence: 99%
“…Recent observations in erythrocyte responses to shear stress suggest that not all blood cells respond equally to The International Journal of Artificial Organs 42 (3) shear history; the working hypothesis of this observation is that older cells may be more susceptible to the effects of shear exposure when compared with younger cells. McNamee et al 7 thus contributed a simple experimental model of erythrocyte response to shear stresses known to impact cellular deformability, with a novel approach to explore whether the least dense (young) or most dense (old) cells respond equivalently. These authors present findings supporting that older cells tend to demonstrate higher levels of impaired cell deformability following sublethal shear exposure, and with substantially shorter exposure durations.…”
Section: Overview Of Contributionsmentioning
confidence: 99%